W is for wasted - Grafton, Sue (New York G.P. Putnam's Sons, 2013)
A local PI is gunned down near the beach at Santa Teresa, looking like a robbery gone bad. Another body turns up on the beach six weeks later. He'd been sleeping rough. Probably homeless. No identification. A slip of paper with Millhone's name and number was in his pants pocket. The coroner asked her to come to the morgue to see if she could ID him. Two seemingly unrelated deaths, one a murder, the other apparently of natural causes. But as Kinsey digs deeper into the mystery of the John Doe, some very strange linkages begin to emerge. -
A Marian Wood book.
Includes bibliographical references (pages 485-486).
Keywords: Millhone, Kinsey (Fictitious character) -- Fiction; Women private investigators -- Fiction; Mystery fiction